Conception and characterization of a multi-sensitive composite chitosan-red marine alga-polysaccharide hydrogels for insulin controlled-release. (15th May 2020) - Feki, Amal; Hamdi, Marwa; Jaballi, Imen; Zghal, Slim; Nasri, Moncef; Ben Amara, Ibtissem
Highlights: Polysaccharides composite hydrogels were synthesized and examined for drug delivery. Characterization with FTIR, SEM, thermal and water absorption capacities. Hydrogels are sensitive to temperature, pH and ionic strength. Influence of algal polysaccharide amounts on the hydrogels in vitro degradation. Insulin release rates can be controlled under different pH conditions. Abstract: Hydrogels properties open up many possibilities for medical applications. In the present study, protein drug insulin was selected as a model drug to test the in vitro release behavior of hydrogels based on blue crab chitosan (Cs) and red marine macroalga Falkenbergia rufolanosa polysaccharide (FRP). The FRP/Cs composed hydrogels were characterized in terms of structural, morphological, thermal and antioxidant properties. Data revealed that FRP addition enhanced the water holding capacity and the water uptake percentages, as well as the textural behavior. Moreover, the prepared hydrogels are simultaneous sensitive to pH, ionic strength and temperature as demonstrated in the swelling ratio test. Additionally, hydrogels at pH 1.2 PBS underwent greater degradation, compared to samples immersed in pH 7.4 PBS. Similarly, the kinetics of insuline release, through the FRP/Cs composed hydrogels exhibited higher released amounts in acidic systems. Through this study, the prepared hydrogels provided suitable and promising microenvironment in drugs delivery.